The united latent quality indiсator of Deschampsia antarctica Desv. adaptibility as reflex of current microconditions in the region of Admiral Bay (King George Island, Maritime Antarctic) - N. Miryuta; I. Parnikoza; A. Myryuta; P. Shvydun; J. Smykla; I. Kozeretska; V. Kunakh (Ukrainian Antarctic Journal, 2014)
Plant populations residing in extreme environmental conditions develop adaptation to sudden abrupt environment changes; such plant reaction is known as adaptability. However, different plant populations develop their adaptability with not the same degree of success. To determine such degree, different measurable indices may be chosen, their changes following the same condition changes being not the same. In this investigation we evaluate the adaptability of a unique Antarctic plant - Deschampsia antarctica, the evaluation being based on parameters reflecting three levels of organization: population level (S, vegetation cover), individual level (Ph, biometric), and cellular level (relative DNA content in leaf parenchyma cells). Field material collection has been carried out on the King George Island (Maritime Antarctic) on ice-free area of the Admiralty Bay during the southern summer period of 2005-2006. Six D.antarctica populations have been analyzed. The approaches used have permitted to choose and analyze the interrelations between several indices of adaptability reflecting the population adaptability. The pairwise differences between populations obtained for each pair of indices studied have been taken for determination of the united latent quality indicator describing the adaptability of each population. The value of this indicator is given in points. Such value determines the coordination of reactions for three adaptability indices having been studied in concrete “mosaic” micro-environmental conditions. Such an approach enables to describe the adaptability of D.antarctica populations taking into account the complex of different traits being intensified.